Antimicrobial and Cytocompatible Bovine Hydroxyapatite-Alumina-Zeolite Composite Coatings Synthesized by Pulsed Laser Deposition from Low-Cost Sustainable Natural Resources - OKTAR, FAİK NÜZHET (AMER CHEMICAL SOC, 2020)
Bovine hydroxyapatite (BHA) and BHA blended with clinoptilolite (CLIN) and alumina (Al2O3) coatings were synthesized using pulsed laser deposition (PLD) with a KrF* excimer laser source (lambda = 248 nm, tau(FWHM) <= 25 ns). Physical-chemical characteristics and the potential use of coatings for preventing bacteria adhesion and biofilm formation were investigated. Optimized PLD conditions were selected for coatings with rough morphologies, suitable for good cell adhesion and implant anchorage and good replication of the source target composition. The crystallinity of composite coatings was progressively decreasing with the augment of the Al2O3 and CLIN contents, which in turn can facilitate an efficacious release of active components. Al2O3- and CLIN-containing coatings exhibited high cytocompatibility and specific antibiofilm profiles, preventing the initiation and maturation of bacterial biofilms. Optimum biological activity profiles associated with the use of sustainable and/or inexpensive materials are, in our opinion, of key importance for the future development of performant implant coatings, which should he perfectly compatible with the surrounding tissue while preventing postsurgical endogenous or nosocomial infections.
Keywords: sustainable resources; antibacterial PLD coatings; bovine-origin HA; clinoptilolite and Al2O3 dopants; cytocompatibility; CLINOPTILOLITE; BONE; CRYSTALLIZATION; BIOMATERIALS; SPECTRA; APATITE; IR